Reel love an analysis on the product placement practice in select Filipino movies featuring ABS-CBN loveteams - Agcambot, Dyna Melissa Jane C. (2018)
This mixed method study aimed to find out how product placements are incorporated and to identify the meanings created in select Filipino movies featuring ABS-CBN loveteams in the last five years (2013-2017). The researcher employed the Adapted Meaning Transfer Model by Cristel Russell and Roland Barthes? denotation and Connotation. Russell?s model assisted in understanding how product meanings that are associated to the movies are eventually transferred to the audience, whereas Barthes? Denotation and Connotation guided the study in identifying the use value (or functional value) and exchange value of the integrated product placements in the selected movies. The result showed that advertisers preferred using a visual and a subtle placement when featuring the brands/branded products in movies. These placements are mostly associated with main characters and positive contexts. The significant statements, the denotation and connotations, and the cluster of meanings extracted were also discussed in the results. For future studies, the researcher recommends having a bigger sample size and a longer time frame (e.g. 10-20 years) which will allow varied results. By studying more movies in a longer time frame, future researchers may discover significant changes in the process of how product placements work throughout the years. Future researchers may also conduct experimental research regarding the product placements? role in influencing consumer?s purchase behavior.